Biphasic predators provide biomass subsidies in small freshwater habitats: A case study of spring and cave pools. (23rd July 2017) - Barzaghi, Benedetta; Ficetola, Gentile Francesco; Pennati, Roberta; Manenti, Raoul
Summary: There is increasing attention on how biomass exchanges determine linkages between ecosystems. However, there is limited information on the factors determining the direction and overall magnitude of energy flow, especially in systems where primary producers are limited. In this study we compared two aquatic ecosystems (cave and spring pools) using the biomass exchanges driven by a biphasic predator, the fire salamander ( Salamandra salamandra ). Between 2013 and 2014, we monitored 21 fire salamander breeding sites (12 cave pools and 9 spring pools) and we quantified the larval biomass input–export. The balance between input and export was related to different abiotic and biotic variables. Salamandra salamandra larvae constituted a major component of the animal biomass in both cave and spring pools, and were the most abundant top predator. Light was the most important parameter in constraining predator biomass; biomass export was lowest in the sites that received less light. In cave pools, the biomass balance was negative, while it was positive in spring pools. Our study demonstrates that cave pools are a system with much lower productivity than springs, and their functioning strongly depends on the input of external resources. Predator occurrence may constitute a major trophic subsidy in poorly productive environments. Gradients of abiotic variables such as light incidence can constrain population size of predators and determine a large variation in their biomass balance.